DEVELOPMENT OF THE OPTIONAL COURSE CHEMISTRY OF FOOD - Горинюк, Ольга; Барус, Маріанна; Олянич, Лідія; Скрипська, Ольга (Modern engineering and innovative technologies, 2023)
The work is devoted to consideration of a number of problems and principles that arise before pupils who seek to find answers to important, topical questions in the field of chemistry and beyond. As a solution to this problem, it is proposed to introduce